2012
DOI: 10.1002/chem.201200999
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Diversity Triggered by Intermolecular Interactions between AuIS2 Groups: Aurophilia and Beyond

Abstract: The present study is aimed at elucidating the factors that direct the assembly of a specific family of AuI species. The assembly of AuI centers and dithiocarboxylato or xanthato ligands results in a surprising structural diversity observed by single‐crystal X‐ray diffraction. However, in solution, just evidences for discrete bimetallic [Au2L2] species have been observed. Interestingly, when dithiocarboxylato ligands have been used, a reversible supramolecular assembly has been observed forming the supramolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
(28 reference statements)
0
26
0
Order By: Relevance
“…Recently, Lima et al reported the gold complex [Au{7-( prop-2-ine-1-yloxy)-1-benzopyran}(DAPTA)] (DAPTA = 3,7-diacetyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane) which has a zigzag 1D chain selfassembled via aurophilic interactions. 41 In solution however, only a few oligomeric compounds featuring Au-Au linkages as the primary propagating backbone bond have been reported; [42][43][44][45][46][47][48][49][50] but they are either unstable at ambient temperature, or lack conclusive data supporting higher ordered structures. Common linkers include diphosphines, diacetylides and diisocyanides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lima et al reported the gold complex [Au{7-( prop-2-ine-1-yloxy)-1-benzopyran}(DAPTA)] (DAPTA = 3,7-diacetyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane) which has a zigzag 1D chain selfassembled via aurophilic interactions. 41 In solution however, only a few oligomeric compounds featuring Au-Au linkages as the primary propagating backbone bond have been reported; [42][43][44][45][46][47][48][49][50] but they are either unstable at ambient temperature, or lack conclusive data supporting higher ordered structures. Common linkers include diphosphines, diacetylides and diisocyanides.…”
Section: Introductionmentioning
confidence: 99%
“…3.26 up to 3.28Å for 1a and from 3.25 to 3.34Å for 1b (with the shortest Au2· · ·S21 = 3.245(2)Å and the longest Au1· · ·S9 = 3.339(2)Å). These interactions are somewhat stronger than those observed for a monomeric gold(I) complex with a tribenzothiazolyl phosphine ligand (3.34 -3.46Å) [13] or the intermolecular Au· · ·S contacts responsible for the packing in discrete, bimetallic dithiocarboxylato complexes of Au(I) (3.43 -3.58Å) [14].…”
Section: Crystal and Molecular Structuresmentioning
confidence: 67%
“…Recently, the effect of both aurophilic interactions and the nature of ancillary ligands on the self-assembly of complex molecular systems, as well as on the rich structural diversity found in the family of Au i thio-derivatives, has been studied in detail. 43 …”
Section: Resultsmentioning
confidence: 99%